Impact of E-Marketing on Book Purchase Tendencies: An Empirical Study on University Undergraduate Students - Kabir, Md. Rishad; Hossain, Rashed; ., Al- Amin; Rahman, Md. Mahfuzur; Sawon, Md. Mehedi Hasan; Mani, Lisa (Journal of Ecohumanism, 2024)
Purpose: This study investigates the effects of e-marketing on customer behaviour in book purchases regarding e-mail marketing, social media marketing, and mobile marketing. It also examines the factors influencing the book-purchasing decision and how each e-marketing channel affects customer behaviour. These findings will be essential context for book industry marketers and stakeholders.Methodology: This quantitative analysis was drawn from survey data in which 205 university undergraduate students from 3 public universities were participated. It is designed to determine the customer's level of acceptance of this or that e-marketing strategy. Regression analysis has been employed to test the relationship between e-marketing strategies and book-buying behaviour, and cross-tabulation has been used to detect demographic patterns.Findings: Unlike social media and mobile marketing, e-mail marketing does not affect consumers' intent to purchase books. Regression analysis shows the significance of concentrated marketing campaigns in influencing consumer behaviour.Practical Implication: The study's insights might help those in the book sector improve their online advertising campaigns. Opportunities in the digital book market are increasing, and publishers and merchants may exploit them by targeting specific customer categories with tailored content.Originality: This study contributes to the existing literature by highlighting the different e-marketing strategies that affect people's decisions to buy books and the demographic factors that play a crucial role in creating these effects.